2011
DOI: 10.3945/ajcn.111.013334
|View full text |Cite
|
Sign up to set email alerts
|

Plasma omega-3 fatty acids and incident diabetes in older adults

Abstract: With the use of objective biomarkers, long-chain n-3 FAs and ALA were not associated with a higher incidence of diabetes. Individuals with the highest concentrations of both types of FAs had lower risk of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(105 citation statements)
references
References 41 publications
2
98
1
4
Order By: Relevance
“…Virtanen et al [12] observed that serum n-3 PUFA concentration was associated with a long-term lower risk of type 2 diabetes, but other studies in Western populations reported no association [5,6,10,11]. An association between n-3 PUFA intake and the risk of type 2 diabetes was reported in Asian [15,16] but not in Western populations [6,8,17,18,19,20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Virtanen et al [12] observed that serum n-3 PUFA concentration was associated with a long-term lower risk of type 2 diabetes, but other studies in Western populations reported no association [5,6,10,11]. An association between n-3 PUFA intake and the risk of type 2 diabetes was reported in Asian [15,16] but not in Western populations [6,8,17,18,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation is that there are different levels of n-3 PUFA in Asian and Western populations. Djoussé et al [10] found no association between plasma levels of n-3 PUFAs and the incidence of type 2 diabetes, but did observe a lower risk of type 2 diabetes in participants who were in the highest quartile of 22:5n3 and 22:6n3 plasma concentrations, suggesting that at certain levels, n-3 PUFA might reduce the risk of type 2 diabetes. Blood levels of 22:5n3 and 22:6n3 were 10% higher in the present study when compared to Western populations, and 8% higher than in Western populations in a Chinese study [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on fish consumption and type 2 diabetes are inconsistent: some show that higher dietary intake of omega 3s decreases the risk of type 2, some show no connection, and some even show that higher fish consumption increases the risk of type 2 diabetes [20,21]. It may be that the chemicals in fish can explain these inconsistencies.…”
Section: Chemicals and Omega-3smentioning
confidence: 99%
“…Humans can synthesize most fatty acids de novo but the health-promoting x-3 and x-6 polyunsaturated fatty acids (PUFAs) are exceptions that need to be sourced from the diet (Djoussé et al 2011). Once acquired, simple x-3 PUFAs such as a-linolenic acid can be converted into more complex very-long-chain polyunsaturated fatty acids (VLC-PUFAs) such as arachidonic acid (ARA), and these can be converted back to the simpler species.…”
Section: Essential Fatty Acidsmentioning
confidence: 99%